The legal aspect of procurement system : doctrine of variation order with respect to design and build procurement system - 243537 Masidah Abdul Majid (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana (Pengurusan Kontrak Pembinaan)) - Universiti Teknologi Malaysia, 2007